THE EFFECT OF SPELLING BEE GAME ON STUDENTS’ VOCABULARY ACHIEVEMENT AT SMP NEGERI 17 KENDARI - Arief, Muhammad Ikhdat Sakti; Tambunan, Tambunan; Siam, Siam (Universitas Halu Oleo, 2020)
The purpose of conducting this research is to examine the effect of Spelling Bee game on students’ vocabulary achievement at the second year of SMP Negeri 17 Kendari. The sample of this research was 30 students in the second grade. This research was conducted in pre-experimental research design. Data of this research were collected by giving pre-test and post-test to the students. They were analyzed by using SPSS 16.0 version (descriptive analysis and inferential statistics). The result showed that there was effect of spelling bee game on the students’ vocabulary achievement. It can be seen from the mean score of post-test which was 62.67, while the mean score of pre-test was 43.67. In order to prove the hypothesis, the researcher took the conclusion by comparing the value of Sig (2 tailed) with the significance α value. It showed that the value of Sig (2 tailed) was 0.000 while the significance α value was 0.05. It means that the value of Sig (2 tailed) was lower than the significance α value (0.000 < 0.05) which indicated there was effect of spelling Bee Game on Students’ Vocabulary Achievement.